Italian Lay Associationism in Libya - Locci, Emanuela (2026)
The contribution aims to investigate the dynamics that concurred, in the last century, in the development of the Italian Masonic Institution in Libyan lands. Very little research has been done so far concerning Freemasonry in what was once an Italian colony, probably due to the difficulty in finding archival sources. The Grande Oriente d’Italia was the first Obedience to establish numerous lodges, in the most important cities of Libya. thanks to the study of the archival fonds, it can be stated that after World War I another Italian Masonic obedience, the Serenissima Gran Loggia Nazionale d’Italia, established lodges in Libya.